HIRARKHISITAS KEDUDUKAN PERATURAN MENTERI DENGAN PERATURAN DAERAH DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN DI TINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 2011 - TESANO. SH. A.21211006, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
ABSTRACTThis thesis focuses hirarkhisitas Position Regulation With Local Regulation System InLegislation In Review of Law No. 12 of 2011. From the study authors using normative legalresearch conclusion: that 1). that the position of ministerial regulations have a higher degreeof regulatory regions, because the position of the ministry as an auxiliary body president whoruns a general policy lines that have been determined and the scope of the enforceability of anational ministerial regulation as well as the substance that is regulated in a ministerialregulation is a translation directly from the enactment laws, rules and regulations president.2). that the ministerial decree is a statutory laws and regulations and has levelitas higher thanlocal regulations, so as to enter the ministerial decree in the preamble to